2000
DOI: 10.1074/jbc.275.17.13098
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Functional Characteristics of the Nucleotide Binding Domains of Multidrug Resistance Protein 1

Abstract: Multidrug Resistance Protein 1 (MRP1) 1 is a member of the ATP-binding cassette (ABC) superfamily of transmembrane transporters that has been shown to confer resistance to a variety of natural product type drugs (1-6). The drug resistance phenotype conferred by MRP1 is similar to that resulting from overexpression of P-glycoprotein (P-gp) (reviewed in Refs. 7-9) and is typically associated with an ATP-dependent decrease in drug accumulation and an increase in drug efflux (4, 6). Although both ABC proteins can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
259
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(288 citation statements)
references
References 55 publications
(62 reference statements)
27
259
1
Order By: Relevance
“…Thus, our present observations suggest that the CL7 Pro 1150 mutation somehow compromises the ability of NBD2 to hydrolyze ATP and/or trap ADP in the presence of vanadate and BeF. This could contribute, at least in part, to the moderately reduced ability of the P1150A mutant to transport LTC 4 , because previous studies have indicated that ATP binding/ hydrolysis at NBD2 plays a dominant role in the transport of this substrate (46,56). However, it is not immediately obvious how reduced ATP binding/hydrolysis activity at NBD2 can be reconciled with the enhanced ability of the P1150A mutant to transport E 2 17␤G and MTX.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Thus, our present observations suggest that the CL7 Pro 1150 mutation somehow compromises the ability of NBD2 to hydrolyze ATP and/or trap ADP in the presence of vanadate and BeF. This could contribute, at least in part, to the moderately reduced ability of the P1150A mutant to transport LTC 4 , because previous studies have indicated that ATP binding/ hydrolysis at NBD2 plays a dominant role in the transport of this substrate (46,56). However, it is not immediately obvious how reduced ATP binding/hydrolysis activity at NBD2 can be reconciled with the enhanced ability of the P1150A mutant to transport E 2 17␤G and MTX.…”
Section: Discussionsupporting
confidence: 48%
“…-enriched membrane vesicle proteins were photolabeled with 8-azido-[␣-32 P]ATP essentially as described (46,47). Briefly, membrane vesicles (20 g) were dispersed in 20 l of transport buffer containing 5 mM MgCl 2 and 5 M 8-azido-[␣-32 P]ATP (1 Ci).…”
Section: Photolabeling Of Mrp1 By 8-azido-[␣-32 P]atp-mrp1mentioning
confidence: 99%
“…For some ABC transporters, the 'choice' of which NBD hydrolyses first may be stochastic [65]. For others, there is a clear asymmetry: for MRP1, NBD2 appears to hydrolyse ATP initially [66,74], and in CFTR, hydrolysis of one ATP is much slower than the other [84]. Nevertheless, the net result is the same: destabilisation of the 'closed dimer' albeit with different kinetic control.…”
Section: Stoichiometry Of Atp Binding and Hydrolysismentioning
confidence: 99%
“…Thus in contrast to certain ABC proteins NBD1 of SUR apparently does not hydrolyze ATP but possesses relatively stable nucleotide binding. Indeed, in the presence of Mg 2+ , NBD1 but not NBD2 of SUR could be labeled with 8-azido [γ-32 P]ATP suggesting that at least one hydrolytic cycle occurred at the second domain prior to labeling leaving the possibility only for tagging of NBD2 with of 8-azido-[α-32 P]ATP [44,45]. Asymmetrical properties of nucleotide interactions with NBDs correlate with the different structural homology between NBDs.…”
Section: Sur Regulatory Module: Nucleotide Binding and Catalysismentioning
confidence: 99%
“…~40% sequence homology of SUR2A and CFTR NBD1s, as well as ~40% between the NBD2s of these two ABC proteins). In the SUR close relatives MRP1 and CFTR NBD2 also typically more catalytically active than NBD1 [44][45][46].…”
Section: Sur Regulatory Module: Nucleotide Binding and Catalysismentioning
confidence: 99%